Intrahepatic sarcomatoid cholangiocarcinoma: A case report of the youngest patient on record and a review of the condition's characteristics - Xi, Long-Fu; Jin, Yun; Li, Jiang-Tao (Frontiers in Surgery, 2022)
As a rare disease, intrahepatic sarcomatoid cholangiocarcinoma (s-CCC) represents less than 1% of malignancies of the hepatobiliary system and its main clinical symptoms include abdominal pain and fever. Results of pathological examinations, despite being the “gold standard”, can easily be confused with hepatocellular carcinoma (HCC). This report is about a 32-year-old male patient who was hospitalized due to occupancy of segment V of the liver for three days and had a history of chronic hepatitis B (CHB) over a 20-year span. Magnetic resonance imaging (MRI) showed a 43 mm × 52 mm-sized liver mass in the V segment, with patchy peripheral enhancement during the arterial phase and rapid wash-out during the portal and late phases. A laparoscopic hepatectomy of segment V, along with cholecystectomy, was performed. Histopathological and immunohistochemical examinations indicated a malignant neoplasm that was positive for vimentin and cytokeratin, with these features providing a positive diagnosis for intrahepatic sarcomatoid cholangiocarcinoma. After surgery, an adjuvant therapy of albumin-paclitaxel combined with gemcitabine regimen was given. No recurrence was found six months after the surgery, with follow-up still ongoing. This report aims to improve the awareness, diagnosis, and treatment of s-CCC.